2021
DOI: 10.17555/jvc.2021.38.3.127
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Oclacitinib and Lokivetmab in Dogs with Canine Atopic Dermatitis

Abstract: Canine atopic dermatitis (CAD) is a genetically predisposed inflammatory and pruritic skin disease presenting characteristic clinical features in dogs. Despite oclacitinib and lokivetmab being commonly used, no study has compared their efficacies in CAD. This study aimed to compare the efficacy, safety, and control of CAD-associated pruritus and skin lesions between oclacitinib and lokivetmab. It also investigated whether switching to lokivetmab from oclacitinib or prednisolone had any benefits. Twenty-five cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…In another study evaluating its safety, no abnormal health findings associated with lokivetmab were observed as a result of its use for 6 months (Moyaert et al, 2017). In a study comparing lokivetmab and oclacitinib, no significant difference was found between their antipruritic effects (Lee et al, 2021).…”
Section: Drugs Routinely Used For the Treatment Of Pruritus In Cad Co...mentioning
confidence: 96%
“…In another study evaluating its safety, no abnormal health findings associated with lokivetmab were observed as a result of its use for 6 months (Moyaert et al, 2017). In a study comparing lokivetmab and oclacitinib, no significant difference was found between their antipruritic effects (Lee et al, 2021).…”
Section: Drugs Routinely Used For the Treatment Of Pruritus In Cad Co...mentioning
confidence: 96%
“…This therapy is effective in CAD, except for otitis externa which seems to be resistant to Lokivetmab and only glucocorticoids sufficiently reduce inflammation of the ear canal. Moreover, side effects of Lokivetmab have also been described, and they include drowsiness, vomiting, diarrhea, lack of appetite, pain at the injection site, dermatitis, and pruritus [ 27 , 28 ].…”
Section: Treatment Of Cadmentioning
confidence: 99%
“…Interleukin (IL)‐31 is now known to represent one of the key cytokines of human and canine AD 3–5 . In dogs with AD, a significant reduction in pruritus has been seen following injections of lokivetmab (LKV, Cytopoint; Zoetis), a therapeutic monoclonal antibody (mAb) targeting canine IL‐31, thus confirming that this cytokine plays a pivotal role in the genesis of pruritus associated with this disease 6–12 …”
Section: Introductionmentioning
confidence: 96%
“…[3][4][5] In dogs with AD, a significant reduction in pruritus has been seen following injections of lokivetmab (LKV, Cytopoint; Zoetis), a therapeutic monoclonal antibody (mAb) targeting canine IL-31, thus confirming that this cytokine plays a pivotal role in the genesis of pruritus associated with this disease. [6][7][8][9][10][11][12] Despite documented therapeutic success in clinical trials, increasing evidence suggests that IL-31 is not required for the induction of acute allergic skin…”
Section: Introductionmentioning
confidence: 99%